2006
DOI: 10.1104/pp.105.076059
|View full text |Cite
|
Sign up to set email alerts
|

A Transcriptome-Based Characterization of Habituation in Plant Tissue Culture

Abstract: For the last 50 years, scientists have recognized that varying ratios of the plant hormones cytokinin and auxin induce plant cells to form particular tissues: undifferentiated calli, shoot structures, root structures, or a whole plant. Proliferation of undifferentiated callus tissue, greening, and the formation of shoot structures are all cytokinin-dependent processes. Habituation refers to a naturally occurring phenomenon whereby callus cultures, upon continued passage, lose their requirement for cytokinin. E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
57
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 105 publications
8
57
0
2
Order By: Relevance
“…Considering these findings, one can suggest that the homologues of the three key proteins in a His/Asp phosphorelay are expressed in Citrus, as well as the response regulators. Those results are quite in agreement with the genes that have been identified in Arabidopsis and other eukaryotes such as yeasts (Pischke et al, 2006).…”
Section: Cytokinin Signaling Pathway In Citrussupporting
confidence: 92%
See 1 more Smart Citation
“…Considering these findings, one can suggest that the homologues of the three key proteins in a His/Asp phosphorelay are expressed in Citrus, as well as the response regulators. Those results are quite in agreement with the genes that have been identified in Arabidopsis and other eukaryotes such as yeasts (Pischke et al, 2006).…”
Section: Cytokinin Signaling Pathway In Citrussupporting
confidence: 92%
“…CytokininIndependent 1 (CKI1) belongs to a group of putative plant histidine kinases whose members do not appear to act as ethylene receptors (Pischke et al, 2006). The regulators are named AHPs (from 1 to 5, Arabidopsis thaliana histidine phototransmitter) and ARRs classified in A-type and Btype Arabidopsis thaliana response regulators (Oka et al, 2002).…”
Section: Cytokinin Signaling Pathwaymentioning
confidence: 99%
“…Cycle conditions were 95°C for 5 min followed by 40 cycles of 95°C for 10 s, 58°C for 7 s, and 72°C for 20s. The expression of reference genes or K + transporter genes was analyzed with gene-specific pairs of primers: ACT2 (Pischke et al, 2006), 5#-GCATGAAGATCAAGGTGGTTGCAC-3# and 5#-ATGGACCTGACTCATCGTACTCACT-3#; UBQ10 (Czechowski et al, 2005), 5#-GGCCTTGTATAATCCCTGATGAATAAG-3# and 5#-AAAGAGATAA-CAGGAACGGAAACATAGT-3#; AtHAK5 (Qi et al, 2008), 5#-CGTTTTCATT-GTTCTTCAGG-3# and 5#-ATCTTCTGGTTCTTGGTTTG-3#; AtCHX17, 5#-CCGTCCCGATATAATCTGCGTTTTC-3# and 5#-CAACGCGTGTTCCA-GAGGATTC-3#. The sequences of the primers for AtCHX17 were designed using the AtRTPrimer program (Han and Kim, 2006).…”
Section: Quantitative Rt-pcrmentioning
confidence: 99%
“…A transcriptome-based analysis of habituated and non-habituated Arabidopsis thaliana plant cell cultures revealed the differential expression of more than 800 genes, including a 19-fold up-regulation of the transcript encoding the cytokinin receptor CRE1. The alterations in gene expression found among habituated and nonhabituated callus cultures do not result simply from global hypomethylation of DNA (Pischke et al 2006). Nevertheless it has been reported that treatment of in vitro cultured cells of a nontumorous Nicotiana glauca 9 N. langsdorffii hybrid with 5-azacytidine, a drug causing hypomethylation, leads to the induction of a habituated phenotype (Durante et al 1989).…”
Section: Habituationmentioning
confidence: 99%